Protocol for an observational cohort study on psychological, addictive, lifestyle behavior and highly prevalent affective disorders in primary health care adults - Méndez-López, Fátima; Oliván-Blázquez, Bárbara; Domínguez-García, Marta; Bartolomé-Moreno, Cruz; Rabanaque, Isabel; Magallón-Botaya, Rosa (Frontiers in Psychiatry, 2023)
Background: Depression and anxious symptoms are prevalent in the general population, and their onset and persistence may be linked to biological and psychosocial factors, many of which are lifestyle-related. The way we manage our care, physical and emotional health and/or discomfort is highly influenced by our own abilities, skills and attitudes despite life's circumstances. The main aim of this protocol to analyse the relationship between psychological constructs (self-efficacy, activation, health literacy, resilience, personality traits, sense of coherence, self-esteem), and the presence of affective-emotional problems (anxiety, depression) and addictions in primary health care. Methods: This is a protocol of a prospective longitudinal cohort study including people of 35-74 years old of Aragon primary health care centers (Spain). Three evaluations will be conducted: baseline evaluation, and follow-up assessments five and ten years after recruitment. The primary outcomes will be severity of depression, severity of anxiety, and addictive behaviours. A detailed set of secondary outcomes will be assessed across all three assessments. This will include psychosocial or personal factors on health behaviour, social support, lifestyle patterns, quality of life, the use of health and social resources, and chronic comorbid pathology. Discussion: The analysis of the impact of psychological constructs and lifestyles on the mental health of people and communities will provide evidence that will make it possible to better address and prevent these prevalent problems and address their improvement from a more global and holistic perspective. The evaluation of psychological constructs should be incorporated into health services to improve people's ability their self-care, the level of knowledge of managing their disease and their physical, mental and social health. Trial registration: ISRCTN Registry; ISRCTN12820058. Retrospectively registered.